Children in conflict with the law their socio-demographic profile, resocialization, and life aspirations - Desullan, Jose Ygnacio Surilla
The study sought to identify and describe the socio-demographic profile, resocialization processes, and life aspirations of Children in Conflict with the Law (CICL). Twenty four (24) respondents aged 9 - 18 years were purposively selected from the Dalayunan, A Home for Boys, a center for youth offenders, in Barrio Obrero, Lapaz City., One-on-one interview using six (6) interview schedules were administered to study the variables under investigation. Results revealed that the CICL committed offenses at the mean age of 14, generally Roman Catholic in religion, mostly middle-born child who have low educational attainment and committed less grave criminal offense/s. Furthermore most of them came from big families having parents with low educational background and with low paying jobs. On the other hand, majority of the respondents have negative self concepts. Basketball and sleeping were the preferred group and solitary leisure activities respectively. Their lives inside the center revolve around skills training, educational, religious, and leisure activities. Intrinsic aspirations were greatly valued and viewed to be most attainable compared to extrinsic aspirations.